A Novel Objective Method of Estimating the Age of Mandibles from African Elephants (Loxodonta africana Africana). - Fiona J Stansfield (PLoS ONE, 2015)
The importance of assigning an accurate estimate of age and sex to elephant carcasses found in the wild has increased in recent years with the escalation in levels of poaching throughout Africa. Irregularities identified in current ageing techniques prompted the development of a new method to describe molar progression throughout life. Elephant mandibles (n = 323) were studied and a point near the distal dental alveolus was identified as being most useful in ranking each jaw according to molar progression. These 'Age Reference Lines' were then associated with an age scale based on previous studies and Zimbabwean mandibles of known age. The new ranking produced a single age scale that proved useful for both male and female mandibles up to the maximum lifespan age of 70-75 years. Methods to aid in molar identification and the sexing of found jaws were also identified.